Sistem Pendukung Keputusan Kelayakan Penerima Program Keluarga Harapan (PKH) Menggunakan Metode TOPSIS dan Metode WP - Ade Riani; Nurahman (Politeknik Negeri Cilacap, 2020)
Program Keluarga Harapan (PKH) is a program from the Indonesian government in the form of providing conditional social assistance to families or poor people who are registered in the integrated data for the poor handling program. As for recipients of assistance can be assessed from several criteria including building area, type of floor, type of wall, defecation facility, source of drinking water, source of lighting, type of fuel for cooking, frequency of buying meat and chicken in a week, frequency of eating in a day , The number of sets of new clothes purchased in a year, access to health centers, access to employment, the latest education of household heads and ownership of several assets. In this study will build a decision support system with calculations using the Technique For Orders Reference by Similarity to Ideal Solution Method (TOPSIS) and Weighted Product Method (WP). Then the final results of this study can be used as an alternative priority for the government in sorting based on the calculation results of the criteria of each family or PKH beneficiar